The Problem of Argumentation in the Questions of Narration Al Sahil and Al Shahij “as a Model” - Alazmi, Khalaf Motlaq; Almutairi, Ahmad Hamad (Dirasat: Human and Social Sciences, 2025)
Objectives: This research aims to study the theme of questions that are pervasive in the narrative of Al-Sahil and Al-Shahj, considering them as interconnected units in the construction of the narrative and its narrative style. Methods: The study required following an analytical descriptive approach based on tracking the instances of questions and exploring their contents. The narrator presented these questions from the beginning of the narrative in the initial dialogue among a group of animals until the emergence of the real narrator at the conclusion of the narrative. Results: The narrative questions involved six characters who shifted roles and topics, led by the hero "Al-Shahj" in diverse discussions. The real narrator's intellectual and philosophical depth was apparent throughout, as Abu Al-Ala navigated debates, paradoxes, humor, and various narrative and poetic styles while addressing heritage. Conclusions: The conclusion of the research focused on exploring questions posed by various characters, which revealed aspects of the narrator's world through conflicts and debates, highlighting societal class distinctions. It emphasized the narrator's interaction with multiple cultural levels and the use of main characters to present diverse ideas, contrasting with secondary characters who offered moments of calm and relief. The questions acted as a neutral narrator, suggesting the presence of the real narrator and Abu Al-Ala's control over the narrative directed at the prince. The study's extensive literary references encourage further independent exploration due to their significant and enriching content.